Local Governance in Nepal: A Study of Machhapuchhre Rural Municipality, Kaski - Dahal, Girdhari (Journal of Political Science, 2021)
The election of the local government was held in 2017 after 20 years and paved the way of practicing local governance. This paper aims to study governance practices in Machhapuchhre rural municipality and analyze its key performances. It is based on the sources of primary and secondary data. The municipality has formulated 15 acts, 4 regulations, 27 codes of conducts, 2 directives during these three years of democratic exercise at local level. This municipality also developed various infrastructures including provision of teaching in Magar language as mother tongue in a primary school. Despite these, the municipality is facing shortage of human and financial problems.